Paediatric forearm refractures- management and outcome: a prospective study - Kuloor, Subraya B.; Mattam, Anoop J.; Shareef, Abdul J.; Sudeep, Anupam (International Journal of Research in Orthopaedics, 2019)
Background: Forearm fractures are one of the commonest injuries accounting for 40% of paediatric fractures with a refracture rate of nearly 5%. Forearm refractures are increasing probably due to poor bone mineralization as a result of decreased physical activity, Vitamin D deficiency. These are treated by conservative measures with closed reduction and casting or by surgical fixation with flexible nails or plates. There are no definitive guidelines for management of forearm refracture and implant removal. Methods: The study is aimed at the epidemiology, methods and difficulties of management and functional outcome of forearm refracture treatment. A prospective study of all the cases of forearm refracture who presented to our institution from 2010 to 2016 with refractures treated either by conservative methods or by IMN. All cases were followed up for 2 years and functional outcome was assessed serially according to price et-al criteria. Results: Our study contained 17 males and 8 females between 6 years and 14 years. 76% refractures occurred before 16 weeks and majority had only tricortical union at this time. 42% patients underwent surgical fixation following refracture. Price et al criteria showed excellent results in 72% of patients. Conclusions: Forearm refractures in children can be treated both conservatively and surgically like a primary fracture depending on the indications but needs 2 to 3 more weeks of immobilization. A good functional outcome was obtained in majority of the cases. We suggest using splints till quadricortical union is achieved to prevent chances of refracture.